Clinical Nurse Specialist: A Critical Member of the ICU Team. Issue 6 (20th May 2021) - Gabbard, Erika R.; Klein, Deborah; Vollman, Kathleen; Chamblee, Tracy B.; Soltis, Lisa M.; Zellinger, Mary
Abstract : Supplemental Digital Content is available in the text. Abstract : OBJECTIVES: To describe the role of the clinical nurse specialist, an advanced practice registered nurse in the intensive care setting. The value and impact of the clinical nurse specialist role as a member of the ICU is presented along with a review of clinical nurse specialist education, licensure, and certification requirements as well as a description of the clinical nurse specialist role, scope of practice, and competencies. In addition, a selected review of clinical nurse specialist–led quality improvement and research that resulted in improved patient outcomes is provided. DATA SOURCES: Review of published medical and nursing literature and expert opinion guidance from a collaborative effort between the Society of Critical Care Medicine, American Association of Critical Care Nurses, and National Association of Clinical Nurse Specialists. STUDY SELECTION: Not applicable. DATA EXTRACTION: Not applicable. DATA SYNTHESIS: Not applicable. CONCLUSIONS: The utilization of a clinical nurse specialist, an advanced practice role, in the ICU is a unique and valuable approach for organizations who strive to move evidence into sustainable practice and drive quality through an interprofessional approach. The valuable contributions made by the clinical nurse specialist efficiently and effectively meet the needs of patients, clinicians, and organizations while improving patient outcomes and optimizing cost avoidance strategies, which further lower economic demands on the healthcare system.